Występowanie zwierząt w pofragmentowanym środowisku leśnym – wpływ czynników w skali wyspy i krajobrazu - Banul, Rafał; Borkowski, Jakub; Kosewska, Agnieszka (Leśne Prace Badawcze, 2018)
To date, in research, the main determinants influencing animal assemblages in fragmented forests have been considered to be forest island area and degree of isolation. Such a simplistic approach may have detrimental effects on the obtained results and conclusions, since there are a large number of other factors determining animal persistence in forest islands. In order to identify these factors and evaluate their importance, we reviewed the scientific literature on the topic. In addition to the island area, also patch shape, edge effects and local plant community structure are crucial factors affecting animal assemblages at the forest island scale. At the landscape scale, the total number of forest islands and their combined area, matrix permeability, occurrence of wide ecological corridors as well as isolated trees and woodlands appear to be the most significant factors. Our review further indicates that many of these elements also tend to interact. For instance, edge effects may reduce the area of suitable habitat in a forest patch. Furthermore, some fragmentation effects may be masked by species traits e.g. mobility, food preferences or habitat specialisation. The landscape context also plays a crucial role in animal persistence in fragmented forests. We thus conclude that there is a strong need to investigate the above-mentioned components of habitat fragmentation at the local and landscape scale using appropriate bio-indicators.